ANALISIS FAKTOR YANG MEMPENGARUHI KEMAMPUAN PERTOLONGAN PERTAMA LUKA BAKAR SETELAH PEMBERIAN EDUKASI - Didit Damayanti; Dwi Setyorini (Universitas Prima Indonesia, 2023)
Burns are one type of wound caused by extreme temperatures or heat that occurs in human activities. Good or bad first aid for burns is greatly influenced by each person. is to analyze the factors that most influence the community's ability to perform first aid for burns in Campur Village, Gondang District, Nganjuk Regency. The research design in this study was logistic regression. The sample size of 40 respondents was selected by purposive sampling, the data were analyzed using logistic regression tests. The results of the logistic regression test showed that the educational factor resulted in a p-value of 0.000 with an OR of 0.192 and a 95% CI of 0.14 – 2.622, which means that education is the factor that most influences the ability of first aid in the management of burns. A person's level of education can affect the process of learning. A person who has a high level of education has more knowledge. The level of education can affect a person's ability to perform first aid for burns. Through education, a person will get more knowledge. A person's educational level relates to the person's ability to understand the information received.